SME suppliers and the challenge of public procurement: Evidence revealed by a UK government online feedback facility. Issue 2 (June 2015) - Loader, Kim
Abstract The UK public sector provides an important opportunity for firms to transact business with an attractive customer. However there is concern that public procurement processes place smaller firms at a disadvantage. The views of small firms are under-represented and this paper provides additional, new evidence in order to improve our understanding of their difficulties with public procurement. A UK Government online feedback facility has provided an original, extensive and rich source of material from SME suppliers. It reveals a public procurement process which SMEs perceive to be frustrating and biased against them. Many of the concerns have been reported previously; overly prescriptive qualification criteria, poorly written tender specifications and prohibitive resource requirements remain the most common barriers but the need to supply via a third party is emerging as a new concern. Contract size, contract length and supplier rationalization did not feature as much as expected. Overall, SMEs are concerned about public procurement practices and the competence of public procurement officers. Whilst the UK government is implementing a series of measures, targeted to address these concerns, further research is required to determine their scope and impact.